2020
DOI: 10.1101/2020.02.18.954479
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constitutive activation of leucine-rich repeat receptor kinase signaling pathways by BAK1-interacting receptor-like kinase 3 chimera

Abstract: 194 words) Receptor kinases with extracellular leucine-rich repeat domains (LRR-RKs) form the largest group of membrane signaling proteins in plants. LRR-RKs can sense small molecule, peptide or protein ligands, and may be activated by ligand-induced interaction with a shape complementary SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASE (SERK) coreceptor kinase. We have previously shown that SERKs can also form constitutive, ligandindependent complexes with the LRR ectodomains of BAK1-interacting receptor-like kinas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…Our results based on native expression of chimeric receptors derived from paralogous proteins showed that ectodomains of NFR1 and CERK6 contain major determinants for ligand perception and signaling specificity that can be further modulated by their intracellular regions. Similar modulation of specificity in the final signaling output by the intracellular domains has been observed with Leucine-rich repeat receptor kinases (34).…”
Section: Lysm Ectodomains Are Critical For Nodulation and Immunitysupporting
confidence: 64%
“…Our results based on native expression of chimeric receptors derived from paralogous proteins showed that ectodomains of NFR1 and CERK6 contain major determinants for ligand perception and signaling specificity that can be further modulated by their intracellular regions. Similar modulation of specificity in the final signaling output by the intracellular domains has been observed with Leucine-rich repeat receptor kinases (34).…”
Section: Lysm Ectodomains Are Critical For Nodulation and Immunitysupporting
confidence: 64%
“…A recent study reported that the extracellular LRR domain of BIR3 fused to the cytoplasmic kinase domains of the SERK‐dependent BRI1, HAESA and ERECTA formed tight complexes with endogenous SERK coreceptors in the absence of ligand stimulus, resulting in a strong gain‐of‐function phenotype when expressed (Hohmann et al ., 2020). We generated the chimeric constructs BIR3‐EMS1, BIR3‐NILR1 and BIR3‐BRI1 as reported (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An engineered‐inducible dimerization (RiD) receptor system can trigger a receptor‐specific RLK signal independently of their cognate ligands or endogenous receptors (Kim et al ., 2021). Another study has indicated constitutive activation of BIR3 fused to the cytoplasmic kinase domains of the SERK‐dependent RLKs in the absence of the ligand (Hohmann et al ., 2020). In the present study, we generated chimeric receptors using the ECDs and ICDs of NILR1, EMS1 and BRI1 as well as the ECDs of AtBRI1 and ICDs of NILR1 of other plants.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, we tested whether BRI1 kinase acHvity is not only necessary but also sufficient to confer bri 3 rescue. To this end we introduced a consHtuHvely acHve chimeric receptor composed of the BAK1-INTERACTING RECEPTOR-LIKE KINASE 3 (BIR3) extracellular domain and the intracellular BRI1 kinase domain (BIR3 EXT BRI1 INT ) (Hohmann et al, 2020) into the bri 3 background. The BIR3 EX BRI1 INT chimera can trigger strong gain-of-funcHon phenotypes that mimic brassinosteroid pathway hyperacHvity (Hohmann et al, 2020).…”
Section: Gene Body-intrinsic Dna Sequences Drive Trace Ubiquitous Bri...mentioning
confidence: 99%